Phytoremediation Technology Using Water Lettuce (Pistia stratiotes) and Blood Cockle Shell Biofilters (Anadara granosa) in the Treatment of Aquaculture Waste - Kartini, Nidya; Delis, Putu Cinthia; Putriani, Rizha Bery; Eka Putri, Septi Malidda (ICSIGER- International Conference on Science and Emerging Technology, 2025)
Aquaculture activities with high stocking densities produce liquid and solid waste rich in organic matter, turbidity, and suspended solids. This study aimed to evaluate the effectiveness of the aquatic plant water lettuce (Pistia stratiotes) as a phytoremediator and the blood cockle shell (Anadara granosa) as a biofilter in treating aquaculture wastewater to enhance water quality and reduce nutrient loads. The research employed a Completely Randomized Design (CRD) with two factors: water lettuce density and observation time. Three treatments and three replications were conducted for 30 days. Water quality parameters measured included temperature, pH, dissolved oxygen (DO), nitrate, ammonia, and phosphate. The results showed that the combination of water lettuce and blood cockle shell biofilters with ten clumps of water lettuce was more effective in reducing phosphate levels, while five clumps were more effective for nitrate reduction. Both treatments produced similar plant growth performance, indicating flexibility in system design.